Isolation of circulating human monocytes with high purity for proteomic analysis - González Barderas, María; Gallego Delgado, Julio; Mas, Sebastian; Duran, Mari Carmen; Lázaro, Alberto; Hernández Mérida, Sergio; Egido, Jesús; Vivanco, Fernando (My University, 2024)
We describe a simple method for isolation of human blood monocytes with the high purity (95¿98%) required for proteomic analysis, which avoids contamination by other blood cells (platelets and lymphocytes) and the most abundant plasma proteins (albu min and immunoglobulins). Blood monocytes were purified by gradient centrifugation followed by positive selection with specific monoclonal antibodies coupled to para magnetic beads. The elution conditions of the positive selection step were modified to avoid contamination with albumin. This method is compatible with flow cytometry which was used to assess the purity of the cell population. From 28 mL of blood, 107 monocytes with . 96% purity are routinely obtained. From the isolated monocytes 200¿250 mg of protein could be recovered. The whole method can be performed in three hours. Similar results were obtained using a negative selection step but with lower purity (92%), increased cost and longer time. After solubilization of monocytes, the proteins were analyzed by two-dimensional gel electrophoresis (2-DE) in the 3¿10, 4¿7, 6¿9 and 6¿11 pH range. DNA was the main contaminant that interfered with the 2- DE and it was removed by treatment with DNAse. Image analysis of gels allowed the reproducible detection and quantification of 1500 spots in the 4¿7 pH range and more than 2000 spots in total by combining (overlapping) 2-D gels in the 4¿7, 6¿9 and 6¿11 pH range. This method is useful for clinical studies of monocytes from a large number of patients due to its rapidity and reproducibility, which permits comparative analysis of normal versus pathological samples and which allows follow up of the expressed proteins of monocytes from each patient. Keywords: Human monocytes / Isolation method / Proteomic analysis / Two-dimensional gel electrophoresis